New irrigated lowland rice variety FOFIFA 187 with a high yield potential released in Madagascar - CGIAR Research Program on Rice (2021)
Old varieties dominate the rice production system in Madagascar. In 2019, four new varieties were released for irrigated systems including FOFIFA 187.